Knowledge and attitudes regarding iron deficiency anemia towards consumption of high iron foods, enhancers, and inhibitors among Youth Red Cross - Farahdina Amelia Rahmah; Izka Sofiyya Wahyurin; Katri Andini Surijati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2026)
ABSTRACTBackground: Youth Red Cross (YRC) members often get information about anemia, so they are considered to have better knowledge and attitudes than non-members. The knowledge and attitudes of YRC members may have influence the consumption of high-iron foods, enhancers, and inhibitors to prevent anemia.Objectives: This study aims to determine the correlation between knowledge and attitude regarding iron deficiency anemia towards the consumption of high-iron foods, enhancers, and iron inhibitors in YRC members of High School 1 Purwokerto.Materials and Methods: A cross-sectional study involving 58 YRC members in High School 1, Purwokerto. The samples were selected by the proportionate stratified random sampling method. Data were collected using knowledge and attitude questionnaires, then the consumption levels using SQ-FFQ and FFQ. The data were analyzed using the Chi-Square test and Likelihood Ratio.Results: There is no correlation between knowledge regarding iron deficiency anemia towards the consumption of high-iron foods and iron inhibitors (p=0.18; 0.47). In addition, there is also no correlation between attitude regarding iron deficiency anemia towards the consumption of high-iron foods, enhancers, and iron inhibitors (p=0.37;0.16;0.50). However, there is a correlation between knowledge regarding iron deficiency anemia towards the consumption of iron enhancers (p=0.01).Conclusion: There is no correlation between knowledge and attitude regarding iron deficiency anemia and consumption of high-iron foods and iron inhibitors, nor between attitude regarding iron deficiency anemia and consumption of iron enhancers. However, there is a correlation between knowledge regarding iron deficiency anemia with consumption of iron enhancers.Keywords : Anemia; attitudes; enhancer; inhibitor; iron; knowledge